Path following for underactuated surface vessels with disturbance compensating predictive control. (21st April 2020) - Liu, Zhilin; Li, Guosheng; Zhang, Jun; Zheng, Linhe
It is common that underactuated surface vessels sailing on the sea suffer from strong external sea disturbances, such that the large roll motion can be probably caused resulting to the bad performance of path following. In order to realize the coordinate control of the rudder roll stabilization and path following, a robust controller with roll constraints is designed by combining predictive control with disturbance observer. Firstly, the rudder angle operating range is divided in the Serret–Frenet coordination frame, and then linear models corresponding to different equilibrium can be established with heading control and roll dynamics. Secondly, considering external disturbance and unmodeled error as the lumped disturbances, the disturbance observer can be utilized to achieve the real-time feedforward compensation leading to the improved system robustness. Thirdly, the output redefinition method is adopted to transfer the original system into a new minimum phase system. Based on the receding horizon and state prediction strategies of the predictive control, the analytical control law can be obtained, and the linear programming method is used to guarantee the roll constraint for the simplified computational burden. Lastly, the simulations have been carried out to show the good performance of the proposed algorithm with the heading control and roll reduction.